Application for 20% of the L/C price of the first batch steel members - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding application for 20% of the L/C price of the first batch steel members of BRAC University new campus project.